BUKU DODING HALELUYA SEBAGAI SALAH SATU MEDIA PELESTARIAN LAGU RAKYAT SIMALUNGUN DI GKPS SIMALINGKAR - Febri Ridho Sipayung (Grenek: Jurnal Seni Musik, 2018)
This study aims to find out what folk song title Simalungun in Doding book Hallelujah,how is the form of the folk songs and the effectiveness of its conservation through replacementmethod lyrics/poems for the congregation GKPS Simalingkar.This study is based on the theoretical foundation to explain the meaning of HallelujahDoding Books, Media, Preservation, and Folk Songs SimalungunThe method used is descriptive qualitative. The population in this study are allSimalungun folk songs that are in the book Hallelujah Doding the 36 songs and 10 congregationsGKPS Simalingkar. The techniques of Data collection in this study conducted by fieldobservations, literature studies, interviews and documentations.Generally, this research shows that the contribution of 36 folk songs in the bookDoding Simalungun Hallelujah create varied impressions in the book. as well as with the form ofsongs that mostly consists of two parts. And look also the effectiveness of the preservation of thefolk song lyrics Simalungun with replacement method/lyrics towards more religious makeHallelujah Doding books as one of the media in the preservation of the folk song SimalungunGKPS Simalingkar.